Odpowiedzi

2010-03-11T18:21:17+01:00
A. -6+ (-16) - (-3) - 2(-2) = -6 -16 +3 + 4 =-15
b.8 - 8 -0,5+1 - 4+1 = -2,5
c.27-(21-2) + (-12 - 21)=27-19-33=-25
d(1,2 - 0,8 - 0,7) - (6,9 + 0,2 -0,5) +1,8=-1,1-6,6+1,1 = -6,6
2010-03-11T18:26:49+01:00
A) -y+8x-z-2x=-y+6x-z= -6+8(-2)+3=-6-16+3=-19
B) -8y-4z+x-y-2z+1=-9y-6z+x+1= -8(-1)- 4×2-0,5+1=8-8+0,5=0,5
c)9y-(7y+x)+(6x-7y)=9y-7y-x+6x-7y=-5y+5x= -5×3+5×(-2)= -15-10=-25
D) (6a-8b-0,7)- (6,9 +a-5b)+1,8= 6a-8b-0,7 -6,9 -a+5b +1,8=5a-3b-5,8=
5×0,2 -3×0,1-5,8=1-0,3-5,8=1-6,1=-5,1